Management and attitudes of villagers towards boreholes in guineawarm eradication in Akinyele local government Area of Oyo State, Nigeria (2002)
Studies on the management and attitudes of villagers to boreholes as a source of water in guineaworm eradication was carried out in 4 villages, Alagba, Deinlokun, Iware and Idi-omo in Akinyele Local Government Area of Oyo State, Nigeria.The findings showed that the borehole reduced or eradicated the guineawonn disease in villages studied but its reliability and efficiency was threatened by insufficient borehole water (especially in villages with a population exceeding 500) and lack of a maintenance schedule by the local government area. It was concluded that it is necessary to carefully consider the reliability of the borehole and the size and the distribution of the population they will serve before they are constructed, in order that the full benefit of water supply intervention can be achieved